Translation Techniques Of Ellipsis In Conversation Found In The Twilight Novel By Lily Devita Sari - Willyadrian, Renalda, Dr. Dwi Haryanti, M.Hum (2017)
ABSTRACT RenaldaWillyadrian. A320130015. TRANSLATION TECHNIQUES OF ELLIPSIS IN CONVERSATION FOUND IN THE TWILIGHT NOVEL BY LILY DEVITA SARI. Research Paper. School of Teacher and Training and Education, Muhammdaiyah University of Surakarta. April. 2017. The objectives of this research are to classify the types of ellipsis in the Twilight novel and their translation and to explain the translation techniques of conversation that contain ellipsis in the Twilight novel and their translation. The form of this research is descriptive qualitative. The data of this research are all ellipsis and their translation. While, the data source of this research is Twilight novel and their translation. The result of research shows the following items: First, there are five types of ellipsis, they are: 1) Ellipsis the whole clause (8 data or 11,11%), 2) WH-Ellipsis the whole clause (10 data or 13, 89%), 3) WH-Ellipsis part of the clause (6 data or 8, 33%, 4) Yes/no ellipsis the whole clause (36 data or 50%), 5) Yes/no ellipsis part of the clause (12 data or 16,67%). Second, the translation techniques of conversation that contain ellipsis are borrowing, adaptation, deletion, addition, modulation, and literal. Third, the result of the translation quality shows that in translation accuracy, the highest percentage is accurate (989 data or 92,60%), 3), in acceptability, the highest percentage is acceptable (947 data or 88,67%), in readability, the highest percentage is readable (986 data or 92,32%). Key Words: Ellipsis, Translation Technique, Translation Quality